2003
DOI: 10.1242/jeb.00276
|View full text |Cite
|
Sign up to set email alerts
|

The energetics of the trot–gallop transition

Abstract: One of the most obvious locomotory behaviors is gait transition (changing from walk to trot/run and changing from trot to gallop). There have been numerous attempts to explain gait transitions. These include considerations of muscle function (Taylor, 1978(Taylor, , 1985 and bone strain (Biewener and Taylor, 1986;Rubin and Lanyon, 1982), theoretical explanations based on mathematical models (Alexander, 1989;Alexander and Jayes, 1983), psychological factors (Diedrich and Warren, 1995) and engineering models (Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 30 publications
(41 reference statements)
4
62
1
Order By: Relevance
“…The increase in metabolic cost when moving up an incline agrees with previous studies (Armstrong et al, 1983;Bamford and Maloiy, 1980;Bedford et al, 1979;Brooks and White, 1978;Chassin et al, 1976;Clapperton, 1964;Cohen et al, 1978;Dill, 1965;Eaton et al, 1995;Ellerby et al, 2003;Farley and Emshwiller, 1996;Margaria et al, 1963;McDonough et al, 2002;Minetti et al, 2002;Raab et al, 1976;Robbins et al, 1979;Rubenson et al, 2006;Snyder and Carello, 2008;Taylor et al, 1972;Warncke et al, 1988;White and Yousef, 1978;Wickler et al, 2000;Wickler et al, 2003;Wunder and Morrison, 1974;Yousef et al, 1972). The finding that descending a decline is not metabolically cheaper than locomoting on the level, however, is contrary to previous findings (Armstrong et al, 1983;Byrnes et al, 1985;Cohen et al, 1978;Margaria et al, 1963;Minetti et al, 2002;Raab et al, 1976;Robbins et al, 1979;Taylor et al, 1972;White and Yousef, 1978;Yousef et al, 1972).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The increase in metabolic cost when moving up an incline agrees with previous studies (Armstrong et al, 1983;Bamford and Maloiy, 1980;Bedford et al, 1979;Brooks and White, 1978;Chassin et al, 1976;Clapperton, 1964;Cohen et al, 1978;Dill, 1965;Eaton et al, 1995;Ellerby et al, 2003;Farley and Emshwiller, 1996;Margaria et al, 1963;McDonough et al, 2002;Minetti et al, 2002;Raab et al, 1976;Robbins et al, 1979;Rubenson et al, 2006;Snyder and Carello, 2008;Taylor et al, 1972;Warncke et al, 1988;White and Yousef, 1978;Wickler et al, 2000;Wickler et al, 2003;Wunder and Morrison, 1974;Yousef et al, 1972). The finding that descending a decline is not metabolically cheaper than locomoting on the level, however, is contrary to previous findings (Armstrong et al, 1983;Byrnes et al, 1985;Cohen et al, 1978;Margaria et al, 1963;Minetti et al, 2002;Raab et al, 1976;Robbins et al, 1979;Taylor et al, 1972;White and Yousef, 1978;Yousef et al, 1972).…”
Section: Discussionsupporting
confidence: 87%
“…Additional muscle activity means that whole-animal metabolic costs (rate of O 2 consumption, V O2 ) should also increase (Ellerby et al, 2003), assuming that additional costs are met aerobically. Accordingly, increased metabolic costs were found in birds (Bamford and Maloiy, 1980;Ellerby et al, 2003;Rubenson et al, 2006;Snyder and Carello, 2008;Warncke et al, 1988), humans (Dill, 1965;Margaria et al, 1963;Minetti et al, 2002;Yousef et al, 1972), a range of quadrupeds (Armstrong et al, 1983;Bedford et al, 1979;Brooks and White, 1978;Chassin et al, 1976;Clapperton, 1964;Cohen et al, 1978;Eaton et al, 1995;Farley and Emshwiller, 1996;McDonough et al, 2002;Raab et al, 1976;Robbins et al, 1979;Snyder and Carello, 2008;Taylor et al, 1972;White and Yousef, 1978;Wickler et al, 2000;Wickler et al, 2003;Wunder and Morrison, 1974;Yousef et al, 1972) and invertebrates (Full and Tullis, 1990;Tullis and Andrus, 2011) when ascending gradients. Although there are notable exceptions -the marabou stork Leptoptilos crumeniferus (Bamford and Maloiy, 1980), cockroach Gromphadorhina portento (Herreid et al, 1981) and ant Camponotus sp.…”
Section: Introductionmentioning
confidence: 99%
“…In much larger animals (horses), gait shifts may reduce costs of transport and peak musculoskeletal forces (e.g. Hoyt and Taylor, 1981;Wickler et al, 2003). In weasels, we observed walking (at low speed) and bounding (at high speed) both in the wild and in our wheel respirometers.…”
Section: The Journal Of Experimental Biology 216 (4)mentioning
confidence: 61%
“…The metabolic-trigger hypothesis has been argued against (Farley & Taylor 1991;Hreljac 1993;Minetti et al 1994;Brisswalter & Mottet 1996) on the basis that self-selected gait transition can occur at non-energetically-optimal speeds, despite the obvious optimization at slower and faster speeds. More recently, horses have been found to switch repeatedly between trotting and galloping over a narrow range of speeds where galloping is metabolically optimal (Wickler et al 2003). From this, it was concluded that conflicting signals, other than metabolic cost, are probably responsible for the trot-gallop transition.…”
Section: (A) Gait Selectionmentioning
confidence: 99%